Effectiveness of the Teams Games Tournament (TGT) Cooperative Learning Model on Students’ Mathematics Achievement - Karina, Lira; Runtu, Patricia V.J; Maukar, Marvel Grace (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
Students’ limited mastery of algebra remains a persistent obstacle in achieving the expected mathematics competencies. At MTs Negeri 1 Manado, instruction is still dominated by teacher-centered lectures, which often lead to passive learning behavior, declining motivation, and difficulties in understanding mathematical concepts. This study was conducted to examine the effectiveness of the Teams Games Tournament (TGT) cooperative learning model as an alternative approach to improve students’ mathematics achievement. A quantitative approach with a quasi-experimental pretest–posttest control group design was applied. The population consisted of all seventh-grade students, and a random sample of two classes (VII-B and VII-I) was selected. The research instrument comprised five essay-type test items that had been validated by experts (lecturers and teachers) and demonstrated acceptable reliability. The procedure included four main stages: preparation, pretest administration, instructional treatment, and posttest administration, followed by statistical analysis. Data were analyzed using normality and homogeneity tests, independent and paired-sample t-tests, and effect size estimation through Cohen’s d. The results indicated a significant improvement in the experimental group, with the mean score rising from 69.52 to 76.97, corresponding to a large effect size (d = 1.09). These findings confirm that the TGT model is effective in enhancing mathematics learning outcomes. Furthermore, the study highlights the pedagogical potential of TGT in promoting active participation, fostering motivation, and offering an engaging alternative to conventional lecture-based teaching in mathematics classrooms.